Resting energy expenditure is lower in Japanese female athletes with menstrual disorders than in eumenorrheic athletes - Moto, K.; Goshozono, M.; Torii, S.; Namba, A.; Taguchi, M. (The Journal of Physical Fitness and Sports Medicine, 2022)
Menstrual disorders are health problems in female athletes. It has also been reported that amenorrhea can lead to metabolic suppression. However, studies regarding resting energy expenditure (REE) in Japanese female athletes with menstrual disorders are lacking. The purpose of this study was to investigate whether REE was suppressed in female Japanese athletes with menstrual disorders. In total, 22 highly trained intercollegiate athletes participated in this study; and body composition, REE, thyroid and reproductive hormone levels, and nutritional intake levels were measured. Predicted REE (REEp) was calculated using two different equations based on fat-free mass (FFM) and organ-tissue mass measured by dual-energy X-ray absorptiometry (DXA). Individuals with menstrual disorders (MD group) had significantly lower height, body weight, and fat mass than those in the eumenorrheic (EU) group; however, the FFM did not differ between the groups. Both the measured REE (REEm) and REEm adjusted for FFM in the MD group were lower than those in the EU group. The REEm to REEp ratio, which indicates energy deficiency, was also lower in the MD group. In addition, although the MD group had lower triiodothyronine and progesterone levels, they were still within the normal range. Japanese female athletes with menstrual disorders may have lower REE than eumenorrheic athletes, even if thyroid and reproductive hormones are within the normal range.